2017
DOI: 10.4317/jced.53550
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short polyethylene fiber with different weight percentages on diametral tensile strength of conventional and resin modified glass ionomer cements

Abstract: BackgroundThe aim of this study was to investigate the effect of polyethylene fiber on diametral tensile strength of conventional and resin modified glass ionomer cements.Material and Methods60 specimens in 6 groups (n=10) were prepared. In group 1 conventional glass ionomer (Fuji GC) and in group 2 resin modified glass ionomer (Fuji LC) were as control groups. In group 3 and 4 conventional glass ionomers mixed with short polyethylene fibers in proportion of 1 wt% and 3 wt%, respectively. In fifth and sixth gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The diametral tensile strength of Activa in this study ranged from 31.4 to 39.2 Mpa. This is in agreement with Sharafeddin et al (5) , who found that diametral tensile strength of reinforced RMGICs, varied from 31.3 to 35.9.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The diametral tensile strength of Activa in this study ranged from 31.4 to 39.2 Mpa. This is in agreement with Sharafeddin et al (5) , who found that diametral tensile strength of reinforced RMGICs, varied from 31.3 to 35.9.…”
Section: Discussionsupporting
confidence: 93%
“…In order to resemble clinical condition for 6 months, all specimens in both groups were thermocycled for 600 cycles from 5 o C to 55 o C with 30 sec dwell time, and 20 sec transfer time (5,8) . Any specimen showing any degree of dislodgment or separation was rejected and replaced.…”
Section: Group IImentioning
confidence: 99%
See 2 more Smart Citations
“…Sharafeddin et al 21 tested GIC with polyethylene fiber and found that mixing of polyethylene fibers with GIC showed a significant positive influence on diametral tensile strength of the tested glass ionomers. We are in the same opinion with the authors that PP fibers improved some properties of GIC.…”
Section: Discussionmentioning
confidence: 99%